2008 5th IEEE International Symposium on Biomedical Imaging: From Nano to Macro 2008
DOI: 10.1109/isbi.2008.4541020
|View full text |Cite
|
Sign up to set email alerts
|

Classification of dementia from FDG-PET parametric images using data mining

Abstract: It remains a challenge to identify the different types of dementia and separate these from various subtypes from the normal effects of ageing. In this paper the potential of parametric images from FDG-PET studies to aid the classification of dementia using data mining techniques was investigated. Scalar, joint, histogram and voxel-level features were used in the investigation with principal component analysis (PCA) for dimensionality reduction. The logistic regression model and the additive logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…A batch normalization layer and an ReLU activation function were added after each convolution layer. We set all convolutional layer strides to 2 and padding was set to be the same as layer (8) input. The structure of 3DCNN for sMRI and PET The structure of 3DCNN used to extract MRI and pet features is the same, but they do not share parameters.…”
Section: Experiments Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…A batch normalization layer and an ReLU activation function were added after each convolution layer. We set all convolutional layer strides to 2 and padding was set to be the same as layer (8) input. The structure of 3DCNN for sMRI and PET The structure of 3DCNN used to extract MRI and pet features is the same, but they do not share parameters.…”
Section: Experiments Settingsmentioning
confidence: 99%
“…The PET can monitor the changes in glucose metabolism in the human body [7]. Wen et al [8] extracted PET image features and identified AD from healthy controls by logistic regression. For the features of a single modality, the observed feature information usually only is provided from a certain perspective.…”
mentioning
confidence: 99%